(NoPOW)QÆDANNQ PRO {ERLOKA hOLMSA (B/s)E - (NkONAN(B-(NdOJLX(B, (NaRTUR(B,s; (NdMITRENKO(B, (Nm(B. (Na(B.,s; (N{AHOWA(B, (Nk(B. (No(B.,s ((NkI)QÇW (B:s)E (NwESELKA(B,s, 1990)
(NoPOW)QÆDANNQ WÆDOMOGO ANGLÆJSXKOGO PISXMENNIKA PRO SLAWNOZWÆSNOGO DETEKTIWA {ERLOKA hOLMSAs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NaNGL)QÆJSXKA LÆTERATURAs)E -- (NwELIKA bRITAN)QÆQs)E -- 19 - 20 (NST(B.s; (NDETEKTIWIs